Improving Municipal Management for Cities to Succeed : An IEG Special Study - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The purpose of this Independence Evaluation Group (IEG) special study is to illuminate the scale and scope of Bank support for municipal development and to draw specific lessons from the achievements and failures of a sample of individual projects. The study focuses on three dimensions of municipal management: planning, finance, and service provision that figure repeatedly in Bank financed municipal development projects (MDPs). The planning dimension refers to the capacity of a municipality to forecast and oversee its own progress. It includes information systems, monitoring and evaluation (M&E), city planning, and investment strategies. The finance dimension refers to how a municipality manages the resources needed to provide services to its constituents. It covers financial management, own-resource mobilization, access to credit, and private funding. The service provision dimension refers to the capacity of a municipality to manage the services required by city residents and business people through the effective prioritization of investments, management of competitive procurement, and the ability to sustain services through operations and maintenance (O&M).